Rationale and strategies for the development of safe and effective optimized AAV vectors for human gene therapy - Arun Srivastava (Elsevier, 2023)
Recombinant adeno-associated virus (AAV) vectors have been, or are currently in use, in 332 phase I/II/III clinical trials in a number of human diseases, and in some cases, remarkable clinical efficacy has also been achieved. There are now three US Food and Drug Administration (FDA)-approved AAV "drugs," but it has become increasingly clear that the first generation of AAV vectors are not optimal. In addition, relatively large vector doses are needed to achieve clinical efficacy, which has been shown to provoke host immune responses culminating in serious adverse events and, more recently, in the deaths of 10 patients to date. Thus, there is an urgent need for the development of the next generation of AAV vectors that are (1) safe, (2) effective, and (3) human tropic. This review describes the strategies to potentially overcome each of the limitations of the first generation of AAV vectors and the rationale and approaches for the development of the next generation of AAV serotype vectors. These vectors promise to be efficacious at significant reduced doses, likely to achieve clinical efficacy, thereby increasing the safety as well as reducing vector production costs, ensuring translation to the clinic with higher probability of success, without the need for the use of immune suppression, for gene therapy of a wide variety of diseases in humans.